2021
DOI: 10.1364/ol.432497
|View full text |Cite
|
Sign up to set email alerts
|

Deep-ultraviolet photodetector based on pulsed-laser-deposited Cs3Cu2I5 films/n-Si heterojunction

Abstract: All-inorganic lead-free perovskite C s 3 C u 2 I 5 thin films were prepared using pulsed laser deposition. Effects of the substrate temperature, laser energy, and laser frequency on the film structure and optoelectronic properties were studied. A heterojunction photodetector based on C s 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…CsCu 2 I 3 and Cs 3 Cu 2 I 5 can coexist in the as-grown Cs−Cu−I films, 41 and the proportions of Cs 3 Cu 2 I 5 improved significantly as the CsI molar ratio increased, which is consistent with the XRD results. The corresponding optical band gap was calculated using the Tauc equation, 42 as shown in the inset of Figures 4a and S3. Obviously, the optical band gap of Cs−Cu−I films increased as the molar ratio of CsI increased.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…CsCu 2 I 3 and Cs 3 Cu 2 I 5 can coexist in the as-grown Cs−Cu−I films, 41 and the proportions of Cs 3 Cu 2 I 5 improved significantly as the CsI molar ratio increased, which is consistent with the XRD results. The corresponding optical band gap was calculated using the Tauc equation, 42 as shown in the inset of Figures 4a and S3. Obviously, the optical band gap of Cs−Cu−I films increased as the molar ratio of CsI increased.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…2 With [Cu 2 I 5 ] 3− as the photoactive site and Cs + as the isolator to form the 0D electronic structure, the exciton binding energy of Cs 3 Cu 2 I 5 is as high as ∼490 meV, making Cs 3 Cu 2 I 5 desirable for fabricating high-efficiency optoelectronic devices, including LEDs and PDs. 14–19…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The emerging widebandgap ternary cesium copper(I) halides (CsX) 1Ày (CuX) y (X = Cl, Br and I) are demonstrated to have great potential in fabricating high-efficiency optoelectronic devices like lightemitting diodes (LEDs) and photodetectors (PDs). [10][11][12][13][14][15][16][17][18][19] Among the promising copper(I) halides, 0D Cs 3 Cu 2 I 5 shows ultra-high quantum efficiency and excellent environmental stability. It was reported that 0D Cs 3 Cu 2 I 5 exhibited obvious blue emission at 441 nm with a large Stokes shift of B143 nm and high PLQYs of 60% and 90% for thin films and single crystals (SCs), respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal halide semiconductors are promising materials for large-area flexible electronics owing to their processability in solution. In particular, toxic element-free copper-based iodides have attracted attention in photonics and electronics owing to their wide bandgap, p-type conductivity, sharp optical absorption, and excellent luminescence properties. In particular, blue and yellow photoluminescence obtained from Cs 3 Cu 2 I 5 and CsCu 2 I 3 with high efficiency and their applicability as DUV photodetectors and γ-ray scintillators with short decay times were demonstrated. In addition, metal–organic frameworks (MOFs) incorporating the local structure of Cs 3 Cu 2 I 5 were reported with high blue luminescence efficiency . It is inferred that the near-unity PL quantum efficiency of bright blue luminescence in Cs 3 Cu 2 I 5 originates from the unique local structure of the luminescent center; an asymmetric [Cu 2 I 5 ] 3– dimer composed of an edge-shared CuI 3 triangle and a CuI 4 tetrahedron is isolated by Cs + ions to form a pseudo-quantum dot.…”
Section: Introductionmentioning
confidence: 99%